Análise de redes e modulação metabólica associadas a parâmetros bioquímicos e fisiológicos em cultivares contrastantes de arroz sob salinidade - Gomes, Micaelle Ribeiro dos Santos (2022)
Salinity affects the growth and development of rice plants. However, some cultivars display better maintenance of features compared to others. We hypothesized that differential metabolites allow rice plants to acclimate to saline stress avoiding production losses. Thus, the main goal of this work was to relate morphological and biochemical alterations with the modulation of primary metabolites and the network topologies impact of two rice cultivars, Esmeralda (ES) and São Francisco (SF), under saline stress. Hydroponic plants were grown in the absence and presence of 80 mM NaCl. Then, length, dry masses, chlorophylls, carotenoid contents, gas exchange, inorganic ions, lipid peroxidation, hydrogen peroxide, antioxidant enzymes, and metabolite profiles were measured. Data were analyzed using MetaboAnalyst and Cytoscape to multivariates and network correlations. Salt stress promoted reductions of growth, total chlorophyll, carotenoid, CO2 assimilation, and other photosynthetic traits in both cultivars but losses in the SF were lower than in ES. Otherwise, the lipide peroxidation, APX activity, and concentration of Na+ were higher in ES leaves, while SF exhibited higher K+/Na+ in both leaves and roots. Metabolomic identified 48 metabolites as sugars, amino acids, organic acids, and others. Principal component analysis (PCA) showed a clear separation among treatment profiles in both leaves and roots. There was a positive metabolite modulation, especially for SF leaves and roots after salt treatment, corroborated by the t-test. Orthogonal Partial Least Squares Discriminant (OPLS-DA) analysis revealed that in the ES most discriminating were glyceric acid, palatinose, and threonic acid that were positive in leaves while leucine, phenylalanine, and valine were positive in roots. For SF, arabinose, lysine, and mannose were the discriminants for leaves, and methionine, ornithine, and xylitol were the discriminants for roots. The effect of salt severely impacted the network of ES leaves, while SF exhibited higher density and heterogeneity. The networks from root metabolites had more density for both cultivars. The network that included sodium ion revealed several metabolites correlated, in which some of them were confirmed by t-test and OPS-DA. Overall, our data showed that ES presented a metabolic profile negatively impacted by salt stress whilst SF this impact had a positive effect in which several metabolites such as carbohydrates, amino acids, and organic acids were induced under salt treatment leading to a better performance in comparison to ES and corroborated physiological results. Thus, this study provides new insights into the mechanism of acclimatization to salt stress and indicates bases of modulation in primary metabolism in rice cultivars that can be used for genotype selection and genetic breeding programs to develop plants more tolerant to environmental stresses.